Realization of Maritime Safety Regulations Implementation to Provide a Sense of Security for Tourists at Labuan Bajo Port - Simanjuntak, P. Dwikora; Guntoro, R. Herlan; Hidayat, Arif (Meteor STIP Marunda, 2023)
Labuan Bajo Port, situated in West Manggarai Regency, East Nusa Tenggara Province, has experienced a significant surge in tourist arrivals as the primary gateway to Komodo National Park, one of Indonesia's designated super-priority tourism destinations. This increase in maritime tourism activities necessitates strict enforcement of maritime safety regulations to ensure the protection and comfort of domestic and international tourists. This study aims to analyze the realization of maritime safety regulations implementation and its effect on providing a sense of security for tourists at Labuan Bajo Port. A mixed-methods approach combining questionnaire surveys, direct observation, and structured interviews was employed during the research period of [Month–Month Year]. The population comprised tourist vessel operators, port authority officers, and tourists utilizing maritime tourism services at Labuan Bajo. Findings reveal that while the overall compliance rate of tourist vessels with mandatory safety equipment standards reached 78.33%, significant gaps remain in life-saving appliance maintenance (68.50% compliance), crew competency certification (72.00%), and pre-departure safety briefing consistency (65.00%). The results demonstrate that full implementation of maritime safety regulations positively correlates with increased tourist confidence levels, with 82.40% of surveyed tourists reporting enhanced perceptions of safety when safety procedures were visibly enforced. The study concludes that strengthened inter-agency coordination between the Harbormaster Office (KSOP), Tourism Authority, and vessel operators, supported by regular safety audits and crew training programs, is essential to sustain Labuan Bajo's status as a safe and world-class maritime tourism destination.